Breadth and orientation of pie menus for mid-air interaction: effects on upper extremity biomechanics, performance, and subjective assessment. - Mao, Lujin; Ono, Kenta; Qi, Mengyao; Huang, Jinghua; Watanabe, Makoto (Behaviour & Information Technology, 2025)
The number and layout of options within pie menus are crucial for determining the direction of radial swiping in mid-air interactions, influencing the physical demands imposed on users. This research examined six distinct option quantities, referred to as menu breadth, and investigated two layouts, designated as menu orientations. These orientations encompass landscape and portrait formats, with the former positioning a top option centred parallel to the horizontal axis, while the latter situates two top options on either side of the vertical axis. The study employed comprehensive metrics, including muscle activity, wrist movement, user performance, and subjective assessments. Our results indicated that the breadth should be controlled to no more than six to ensure high efficiency and align with users' interactive experience, while breadth 2 should be avoided to eliminate the potential risk of wrist musculoskeletal disorders. Besides, the portrait orientation for breadth 3 and the landscape orientation for breadth 6 were recommended for their lower physiological loads and higher efficiency. Also, the landscape orientation for breadth 4 should be favoured as it outperformed portrait orientation in both wrist movement dimensions. These findings could provide scientific design principles for using pie menus in mid-air interaction within future HCI applications.